Anxiety Disorders, Anxious Symptomology and Related Behaviors Associated With Migraine: A Narrative Review of Prevalence and Impact - Raudenská, Jaroslava; Macko, Tomáš; Vodičková, Šárka; Buse, Dawn C; Javůrková, Alena (Current pain and headache reports, 2025)
PURPOSE OF REVIEW: The purpose of this study was to review the literature on the relationship between migraine, anxiety and related disorders, anxious symptomology and related behaviors. RECENT FINDINGS: Generalized anxiety, other anxious disorders and migraine are comorbid. In addition, anxious symptomology and behaviors are common in people with migraine even if they do not meet diagnostic criteria or threshold. Anxiety including diagnosed disorders such as generalized anxiety, phobias, panic disorder, as well as behaviors such as catastrophizing, avoidance behaviors, and higher fear of headache/migraine or anxiety sensitivity are comorbid and/or common in migraine. Anxiety is associated with negative outcomes such as migraine progression, medication overuse, stigma and migraine-related disability. The association between migraine, anxiety, and fear and avoidance behaviors has an extensive empirical basis. Awareness of the high prevalence of comorbidity and symptomology as well as the negative outcomes associated with anxiety and related symptoms and behaviors is important in the comprehensive management of people with migraine. Better understanding the relationship between migraine and anxiety symptoms and behaviors and their effects on outcomes is essential to provide more effective treatment for people with migraine. The review emphasizes the necessity of screening and more comprehensive evaluation in patients with migraine using psychological diagnostic tools. Thus, prevention and management of anxiety, fear, and anxiety-related behaviors in the context of migraine management may be considered an essential treatment goal and strategies may include non-pharmacological and pharmacological approaches.
Keywords: Anxiety; Comorbidity; Migraine Disorders; Phobias; Cephalalgiaphobia; komorbidita; úzkostné poruchy; lidé; Cogniphobia; Anxiety Disorders; Generalized anxiety disorder; Avoidance; Anxiety sensitivity; Migraine; Humans; strach; prevalence; úzkost; migréna; Prevalence; Fear